Tuning the photochemical properties of unsymmetrical functionalized dimethylaminobenzaldehyde diethylenetriamine / Salamiah Zakaria … [et al.] - Zakaria, Salamiah; Hasan, Sharizal; Kamal, Mohd Lias; Uyup, Noor Hafizah (Research Management Institute (RMI), 2016)
Much effort has been study to the development of chemosensor to determine the chemical species especially fluorescence-based ones. This is because luminescent compounds for chemosensor are usually very sensitive, inexpensive, easily performed, simple preparation, and versatile [1],[2],[3]. Fluorescent chemosensors are very important in a many fields including environmental chemistry, analytical chemistry, and bio-medicinal science. One of the major tasks in sensor development is the design and synthesis of novel receptors with the ability for molecular recognition [4]. Chemosensors are able to bind selectively and reversibly the analyte interest with a concomitant change in the property of the system, such as redox potentials or luminescence spectra. The construction of a fluorescent chemosensor usually involves two integrated components: one is a signaling fluorophore (active unit) and another is a receptor that possesses a recognition capability (receptor unit), both are connected through a spacer. There are many opportunities exist for modulating photophysical properties of a fluorophore. This offers a wide number of possibilities for tailoring efficient luminescent chemosensor. In synthesizing luminescence complexes, organic chromophore will be employed as antenna for light absorption. This chromophore will act as a signal reporting unit in chemosensor. Generally, polyamine complexes show very weak absorption in the visible region and often require the application of strong absorbing antennae for light harvesting to obtain photoluminescence. Diethylenetriaminepentaacetic acid (DTPA) a derivative of polyamine, is a complexing agent for lanthanides conjugated with chromophore as an antenna or sensitizer to absorb the excitation light and overcome the weak absorbance of the lanthanides [5]…